Paroxysmal epigastric pain 30 years after abdominal trauma surgery—a case report - Zhang, Yisheng; Lu, Xin; Xu, Yiyao (Frontiers in Surgery, 2023)
A 58-year-old male was admitted to the liver surgery ward of Peking Union Medical College Hospital as the result of recurrent cholangitis in the past six months. Preoperative abdominal CT and gastrointestinal radiography showed duodenal dilatation and reconstruction of gastrointestinal tract, which might be related to the laparotomy and hemostasis performed due to traffic accident 30 years ago. The operative method of that surgery might be the reason for the patient’s choledocholithiasis and duodenal dilatation.